Novel contribution to existing knowledge: a focus on emotional intelligence and academic behavior in Northern India - ., Shikha; Sarin, Jyoti; Abhishek; Saini, Abhishek; ., Saima; Sharma, Priya; Qurat-Ain; Dogra, Rahul; Hafiz, Rahil (International Journal Of Community Medicine And Public Health, 2024)
Background: The present study explored the relationship between emotional intelligence (EI) and academic behavior (AB) among undergraduate students in Northern Indian colleges. Understanding these factors is fundamental for enhancing student success and well-being. Methods: Using a cross-sectional methodology, self-report questionnaires were used to gather data from 1000 undergraduate students who were selected through purposive sampling. Data was collected using tools that included the Emotional Intelligence Self-Assessment Questionnaire and the Academic Behavior Assessment Questionnaire. Results: The study’s findings indicate that, while emotional intelligence and academic behavior are not substantially associated, students exhibit exceptional academic behavior and high emotional intelligence scores Statistical analyses examined the correlations and impacts of various demographic factors on EI and academic behavior. Participants exhibited high levels of academic behavior (mean=87.26, SD=13.55) and average levels of EI (mean = 48.76, SD = 13.99). A statistically significant positive correlation was found between EI and academic behavior (r = 0.097, p = 0.002). Course of study, presence of physical illness, and socio-economic status significantly influenced academic behavior, while place of residence, religion, and socio-economic status affected EI scores. Conclusions: Despite the positive correlation between EI and academic behavior, the association was not substantial. The study highlights the complex interplay of multiple factors affecting student achievement. Further research is encouraged to investigate additional variables impacting EI and academic behavior among Northern Indian undergraduates. These insights can inform targeted interventions to support student development and academic success.